Lighter as flame control and temperature control in milk pasteurization system - Rizky Alief Febriansyah; Weny Indah Kusumawati; Harianto; Pauladie Susanto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Milk pasteurization involves heating milk at a specific temperature below its boiling point as a method to keep the resulting dairy product retaining the shape and taste characteristics of fresh milk. In several experiments, the use of fuzzy control systems has been tested to regulate the temperature in the milk pasteurization process and to time the ignition of the stove flame. However, this fuzzy approach still causes the system to give an unstable response and irregular stove flame. In order to study milk pasteurization, the Low Temperature Long Time (LTLT) method is used which is implemented automatically through a PID control system. This method serves to maintain nutritional quality by keeping the pasteurization temperature at a setpoint of 62°C. This control involves the use of servo actuators and electric lighters that are automatically regulated with the help of flame sensors. The flame sensor detects the presence of flame and ensures that the flame remains lit throughout the pasteurization process. At the end of the process, the flame sensor plays a role in breaking the flame by setting a certain threshold. This sensor operates within 10 CM of the flame source and will produce an analog output with a maximum value of 4000 when the flame is lit. When the flame is extinguished, the analog output of the sensor will reach a value of 4095. Testing of the milk pasteurization automation system is given a value for each PID resulting from the value of Kp = 31.8, Ki = 115.6, Kd = 4.4 and obtained a rise time value of 0.39 minutes, 0.61%, settling min of 60.88, and settling max of 62.38.